PENGARUH TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 3 PEKANBARU - Ayu Sariani; Raja Arlizon; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the description of students' self-confidence before and after being given a Role Playing technique, differences in students' confidence before and after being given a Role Playing technique and to increase students' self-confidence through group guidance. The research method used is a quantitative method with the type of pre-experimental one group pretest-posttest research. The subjects of this study were eighth grade students of SMP Negeri 3 Pekanbaru with low self-confidence, amounting to 7 people. The instruments of data collection used were questionnaires using a Likert scale. The data analysis technique used is the Non Parametric statistical technique using the Wilcoxon Test and the Spearman Rank Test. The results showed students 'confidence before being given role playing techniques through group guidance were mostly in the low category of 100% and after being given role playing techniques through group guidance students' self-confidence experienced an increase namely in the high category of 71, 40% and in the medium category 28.60%. Based on the Wilcoxon Test there are significant differences in student self-confidence before and after being given role playing techniques through group guidance with a significance value of 0.018 <α 0.05. Based on the Spearman Rank Test, it can be concluded that the relationship between role playing techniques through group guidance and student confidence is in the high category of 0.746 or 56%. Next to find out the detemination coefficient as follows: (rs) 2 = (0.746) 2 = 0.556. This means that the influence of role playin techniques through group guidance services to improve student self-confidence is 56% while 44% is influenced by other factors that originate in students and from the student environmentKey Words: Role Playing, Self Confidence,Group Guidance.